0143 A 10 year prospective study of toner handling workers. (21st August 2017) - Sugano, Ryosuke; Michii, Satoshi; Ando, Hajime; Nozawa, Hiroki; Ikegami, Kazunori; Ogami, Akira
Abstract : Purpose: To measure the risk of pulmonary disease due to toner dust exposure, in a 10 year prospective cohort study among toner handling workers. Methods: Subjects that were included in the analysis of this study were 260 male employees of a Japanese photocopier, printer and toner production company. Onset of pneumoconiosis, pulmonary fibrosis, granulomatous pneumonia and lung cancer were assumed as endpoints of the investigation, and blood markers (KL-6, SP-D), respiratory function index and the chest CT shadow reading were used as substitute end-points for before the onset of these diseases. Disease onset was determined via a self-administered questionnaire, blood tests and respiratory function tests were conducted once a year, while Chest CT examinations were conducted in the 1 st, 5th and 10th year of the study. Subjects were classified by duration of toner handling work into four groups - long-exposure (>20 years): n=65 (mean 40 years, smoking rate 35%); medium-exposure (10–20 years): n=71 (mean age 31.9 years, smoking rate 47.9%), and short-exposure (<10 years): n=50 (mean age 31.6 years, smoking rate 46%). The average dust levels in the environment of the toner handling work decreased well below the ACGIH allowable concentrations through the period of the study. Results: None of the endpoint diseases developed in any of the four groups. Annual percent change for blood marker and respiratory function levels, and chest CT parameters were compared across the four groups but no statistical significance was seen. Conclusion: The risk of developing respiratory disease with the levels of toner dust exposure found in this study was extremely low.